Status on Practicing Weak Hadith Regarding Supplication Narrated From The Prophet PBUH - Mohd Rapingi, A. M.; Ismail, M. Y. (Universiti Sains Islam Malaysia, 2024)
This study focuses on the status of practicing a weak hadith of du'a based on the analysis of two different group of scholars who allows and forbid it. Subsequently, this study come up with the selected opinion between the two group based on various arguments. Research findings indicate that there are vast amount of scholar's opinion on this topic, and this debate has been discussed since the second century of hijra untill today. Among the contributions of this study are collecting the scholars' opinion on the topics of debate, analyze and criticize each of their opinions, and introducing some other appropriate new texts and arguments. The conclusions of this study have chosen the opinion that allows the practicing of the hadith dhaif, however the practice should meet certain requirements that have been set.